Sleep problems in bipolar disorders: more than just insomnia - Steinan, M. K. (Acta Psychiatr Scand, 2015)
OBJECTIVE: Sleep problems in bipolar disorder (BD) are common, but reported rates vary from 10% to 80%, depending on definitions, methodologies and management of potential confounding factors. This multicenter study seeks to address these issues and also compares BD cases with Hypersomnia as well as the more commonly investigated Insomnia and No Sleep Problem groups. METHOD: A cross‐sectional comparison of sleep profiles in 563 BD I and II individuals who participated in a structured assessment of demographic, clinical, illness history and treatment variables. RESULTS: Over 40% cases met criteria for Insomnia and 29% for Hypersomnia. In univariate analysis, Insomnia was associated with BD II depression whilst Hypersomnia was associated with BD I depression or euthymia. After controlling for confounders and covariates, it was demonstrated that Hypersomnia cases were significantly more likely to be younger, have BD I and be prescribed antidepressants whilst Insomnia cases had longer illness durations and were more likely to be prescribed benzodiazepines and hypnotics. CONCLUSION: Whilst Insomnia symptoms are common in BD, Hypersomnia is a significant, frequently underexplored problem. Detailed analyses of large representative clinical samples are critical to extending our knowledge of differences between subgroups defined by sleep profile.